A rare case of dysembryoplastic neuroepithelial tumor combined with encephalocraniocutaneous lipomatosis and intractable seizures - Jee-Yeon Han; Mi-Sun Yum; Eun-Hee Kim; Seokho Hong; Tae-Sung Ko (Korean Pediatric Society, 2016)
Encephalocraniocutaneous lipomatosis (ECCL) is a rare neurocutaneous syndrome that affects ectomesodermal tissues (skin, eyes, adipose tissue, and brain). The neurologic manifestations associated with ECCL are various including seizures. However, ECCL patients very rarely develop brain tumors that originate from the neuroepithelium. This is the first described case of ECCL in combination with dysembryoplastic neuroepithelial tumor (DNET) that presented with intractable seizures. A 7-year-old girl was admitted to our center because of ECCL and associated uncontrolled seizures. She was born with right anophthalmia and lipomatosis in the right temporal area and endured right temporal lipoma excision at 3 years of age. Seizures began when she was 3 years old, but did not respond to multiple antiepileptic drugs. Brain magnetic resonance (MR) imaging performed at 8 and 10 years of age revealed an interval increase of multifocal hyperintense lesions in the basal ganglia, thalamus, cerebellum, periventricular white matter, and, especially, the right temporal area. A nodular mass near the right hippocampus demonstrated the absence of N-acetylaspartate decrease on brain MR spectroscopy and mildly increased methionine uptake on brain positron emission tomography, suggesting low-grade tumor. Twenty-four-hour video electroencephalographic monitoring also indicated seizures originating from the right temporal area. Right temporal lobectomy was performed without complications, and the nodular lesion was pathologically identified as DNET. The patient has been seizure-free for 14 months since surgery. Although ECCL-associated brain tumors are very rare, careful follow-up imaging and surgical resection is recommended for patients with intractable seizures.